Geospatial Perspective in the Distribution and Zoning Model of Senior High Schools in Bandar Lampung City - Utami, Dian; Afrilia, Ayu (Jurnal Penelitian Geografi, 2025)
The school zoning system aims to improve equitable access to education; however, its effectiveness largely depends on the spatial distribution and availability of educational facilities. This study analyzes the spatial distribution and zoning evaluation of 17 public senior high schools in Bandar Lampung City based on the 2024 New Student Admission (PPDB) Technical Guidelines. A quantitative approach was employed using Geographic Information Systems (GIS), including geoprocessing and buffering techniques to map service zones. Data were obtained through documentation and field observations, then analyzed using: (1) Nearest Neighbour Analysis (NNA) to identify distribution patterns, and (2) GIS-based buffering to delineate service areas. The results show: (1) the distribution pattern of public senior high schools is random (NNA value = 1 km), indicating uneven spatial distribution; and (2) buffering analysis within 0–3000 meters identifies both served and underserved areas, particularly in suburban regions such as Panjang, Telukbetung Barat, and Sukabumi. The findings conclude that the 3 km zoning radius is not yet optimal in ensuring equitable access across all areas. Policy recommendations include: (1) establishing new school units in underserved regions, (2) adjusting zoning policies based on spatial analysis, and (3) optimizing school transportation. These results emphasize the need to integrate GIS into spatially based educational planning.